Coordinating multiple representations of polynomials: What do patterns in students' solution strategies reveal?. (June 2017) - Zahner, William; Dai, Ting; Cromley, Jennifer G.; Wills, Theodore W.; Booth, Julie L.; Shipley, Thomas F.; Stepnowski, Waldemar
Abstract: We investigate the strategies used by 64 advanced secondary mathematics students to identify whether a given pair of polynomial representations (graphs, tables, or equations) corresponded to the same function on an assessment of coordinating representations. Participants also completed assessments of domain-related knowledge and background skills. Cluster analysis of strategies by representation pair revealed patterns in the participants' strategy use. Two clusters were identifiable on tasks that required matching equations to graphs and graphs to tables. We identified overlap between these two clusters, suggesting that while the representation pair influenced strategy choice, there was also a general distinction between students who used more and less sophisticated strategies. However, students who used more sophisticated coordination strategies were similar to the others on measures of domain-specific knowledge or background skills. We consider implications for future investigations testing interventions to promote coordinating representations. Highlights: Strategies for coordinating multiple representations of polynomials were identified. Cluster analysis revealed identifiable groups by strategy use on equation-graph and graph-table questions. Overlapping cluster membership indicated patterns of more- and less-sophisticated coordination strategies.